System of role processes and relevant correlates - Jain, Ravindra K.; Juneja, Vibhooti (2003)
It is widely believed while looking at the relevant literature that Action Research Methodology and Technique of participants observation may serve as a useful guide. assessing the attribution process aspects of the role occupant, one may open up a new facet of research. One can explore even the impact of supervisors as role-models on subordinates role-learning. A little attention could be paid to explore the relationship between organizational effectiveness and role effectiveness of the employees. Research contribution on these lines is to be made particularly in India as it appears quite unexplored. The studies on role-process and their linkage with the various dimensions of managerial effectiveness in particular and of organizational effectiveness in general have wide implications in the present context of global competition among the organizations. The present paper attempts to correlate system of role processes with organizational effectiveness. - Reproduced.
Keywords: Organizations